When paroxysmal atrial fibrillation in patients with cerebral stroke requires cardiversion? - Jaxa-Chamiec, Tomasz (Przewodnik Lekarza/Guide for GPs, 2005)
Incidence of atrial fibrillation as well as cerebral stroke increases with age. One of the most serious consequences of atrial fibrillation is the occurrence of cerebral embolism. In the treatment of patients with paroxysmal atrial fibrillation a key question remains whether to restore and maintain sinus rhythm with antiarrhythmic drugs or to control the ventricular rate only. It is known that antiarrhythmic drugs can also act proarrhythmicelly. Recent research emphasises the increasing role of controlling the ventricular rate with simultaneous anticoagulant treatment as a safe and inexpensive method. Pharmacological method of cardioversion is currently much more widely used than in the past.